The Covid-19 pandemic and conflict dynamics in Syria: Neither a turning point nor an overall determinant - Muriel Asseburg; Hamidreza Azizi; Galip Dalay; Moritz Pieper (Stiftung Wissenschaft und Politik (SWP), 2020)
Nine years into the (civil) war, Syria is in an extraordinarily poor position to confront the Covid-19 pandemic. Instead of the pandemic leading towards the uniting of local, regional, and international actors involved in Syria around a common purpose, conflict dynamics have hampered an effective response to Covid-19. Yet, the pandemic is unlikely to become a decisive turning point in conflict dynamics or an overall determinant of its future trajectory. Rather, in the mid-term, the relevant actors are likely to continue to follow their strategic interests in Syria, while some will have to adjust their operational priorities, as well as the strategies to pursue them, against the backdrop of the pandemic. Cooperation among external actors in solving the conflict is not set to get any easier. Trends of destabilisation and erosion of state capacity in the war-torn country are also likely to continue. Europeans should prioritise helping fight the pandemic in all areas of Syria and reengage in diplomacy aimed at conflict settlement and the prevention of military escalation among involved actors.
Keywords: 320